CTAB PROTOCOL OPTIMIZATION FOR HIGH-PURITY DNA EXTRACTION FROM ACIDIC SOIL IN THE HABITAT OF WILD BILBERRY (VACCINIUM MYRTILLUS L.) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
Two modified versions of the cetyltrimethylammonium bromide (CTAB)-based method were compared with a commercial kit to develop a cost-effective and efficient protocol for high-purity DNA extraction from acidic soil in the habitat of wild bilberry Vaccinium myrtillus L. The CTAB-NB (no bead treatment) approach resulted in poor outcomes in both yield and quality (1.56 and 0.37 at absorbance ratios of 260/280 and 260/230). The addition of bead treatment in 0.1 mm PowerBead Tubes (Qiagen), coupled with extended mixing (CTAB-B), increased DNA yield by more than eight times and substantially improved DNA purity, yielding 545.76 ng DNA per g of soil with 260/280 and 260/230 absorbance ratios of 1.87 and 1.62, respectively. The commercial kit provided high-yielded (856.08 ng DNA per g of soil) and pure DNA with a 260/280 ratio of 1.95 and a 260/230 ratio of 2.10. The CTAB-B protocol is cost-efficient and provides high-purity DNA suitable for metagenomic PCR amplification.
Keywords: CTAB; DNA isolation; acidic soil; metagenome; PCR amplification